The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1242/jcs.126888
|View full text |Cite
|
Sign up to set email alerts
|

Membrane curvature generation by a C-terminal amphipathic helix in peripherin-2/rds, a tetraspanin required for photoreceptor sensory cilium morphogenesis

Abstract: SummaryVertebrate vision requires photon absorption by photoreceptor outer segments (OSs), structurally elaborate membranous organelles derived from non-motile sensory cilia. The structure and function of OSs depends on a precise stacking of hundreds of membranous disks. Each disk is fully (as in rods) or partially (as in cones) bounded by a rim, at which the membrane is distorted into an energetically unfavorable high-curvature bend; however, the mechanism(s) underlying disk rim structure is (are) not establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 71 publications
5
53
0
Order By: Relevance
“…Peripherin/rds is a structural protein required for the integrity of the disk membrane structure. Trafficking of peripherin/rds to the evagination is consistent with the role of peripherin/rds in inducing membrane curvature (Wrigley et al, 2000;Kevany et al, 2013;Khattree et al, 2013). Overgrown evaginations, as observed by electron microscopy in this and previous studies (Williams et al, 1988), would require a larger edge with high membrane curvature, to which additional peripherin/rds can contribute.…”
Section: Discussionsupporting
confidence: 88%
“…Peripherin/rds is a structural protein required for the integrity of the disk membrane structure. Trafficking of peripherin/rds to the evagination is consistent with the role of peripherin/rds in inducing membrane curvature (Wrigley et al, 2000;Kevany et al, 2013;Khattree et al, 2013). Overgrown evaginations, as observed by electron microscopy in this and previous studies (Williams et al, 1988), would require a larger edge with high membrane curvature, to which additional peripherin/rds can contribute.…”
Section: Discussionsupporting
confidence: 88%
“…With more than 50 residues, the C-terminal cytoplasmic domains of peripherin/RDS and ROM-1 are, among tetraspanins, exceptionally long. This domain in peripherin/RDS has been suggested to have a fusogenic activity (Boesze-Battaglia et al, 2003) and was recently shown to contain an amphiphatic helix that is able to generate membrane curvature (Khattree et al, 2013), suggesting that there is a direct role of peripherin/RDS in generating the high-curvature bend of the disk rim.…”
Section: Box 2 Specialized Tetraspaninsmentioning
confidence: 99%
“…Although the complete role of peripherin-2 in this process is not yet fully elucidated, the carboxy-terminal domain of peripherin-2 has been shown to play a role in membrane fusion (Boesze-Battagliaa andStefano 2002, 2003), initiation of rim membrane curvature (Khattree et al 2013), and OS targeting (Tam et al 2004;Tian et al 2014). The D2 loop and covalently linked peripherin-2 complexes are required for the maintenance of the flattened rim morphology (Wrigley et al 2000;Chakraborty et al 2009Chakraborty et al , 2010.…”
Section: The Role Of Peripherin-2 Protein In Photoreceptor Morphogenementioning
confidence: 99%